A predictive critical flutter wind speed modeling for long-span bridges. Issue 9 (July 2020) - Lin, Kun; Wei, Minghai; Liu, Hongjun; Wang, Huafeng
In this article, a two-dimensional Lighthill aerodynamic model is first extended to three-dimensional space, and then combined with the larger Von Karman plate deformation theory, a model for predicting the critical flutter wind speeds of long-span bridges in the primary design is proposed. The predictions of the presented model are compared to the results of wind tunnel tests for five long-span bridges with different main girder section forms. After that, based on the proposed model, the effects of width to span ratio and thickness to span ratio on the critical flutter wind speeds of long-span bridges are investigated. The results show that the differences between the proposed model and wind tunnel tests are only 7%–14%. Therefore, the presented model can assess the flutter wind speed in preliminary design stages of a bridge. The results also reveal that width to span ratios between 1/30 and 1/10 and thickness to span ratios between 1/300 and 1/100 are optimal for long-span bridges.